2009
DOI: 10.1063/1.3094320
|View full text |Cite
|
Sign up to set email alerts
|

Small tin cluster anions: Transition from quasispherical to prolate structures

Abstract: The structures and energetics of small tin cluster Sn(n)(-) anions up to n=15 were determined by a combination of density-functional theory and three different experimental methods: Ion mobility spectrometry, trapped ion electron diffraction, and collision induced dissociation. We find compact, quasispherical structures up to n=12. Sn(12)(-) is a slightly distorted hollow icosahedron while Sn(13)(-) to Sn(15)(-) have prolate structures, consisting of merged, hollow, in part incomplete, deltahedral subunits: Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 65 publications
3
57
0
Order By: Relevance
“…Sn 7 is an apparent exception. Whereas Sn 7 is observed as a dominant fragment in collision induced dissociation studies of smaller clusters, 11 it was not found as a discrete structural element ͑pentagonal bipyramid͒ within the medium sized clusters considered here. However, the Sn 7 unit is found as higher energy isomer.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Sn 7 is an apparent exception. Whereas Sn 7 is observed as a dominant fragment in collision induced dissociation studies of smaller clusters, 11 it was not found as a discrete structural element ͑pentagonal bipyramid͒ within the medium sized clusters considered here. However, the Sn 7 unit is found as higher energy isomer.…”
mentioning
confidence: 92%
“…Interestingly, the 15-atom subunit strongly resembles the ground state structure of Sn 15 − . 11 Several low-energy isomers were found, of which only the tentative ground state ͑25-1͒ is shown in Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of ion mobility measurements, it has been concluded that the morphology follows the pattern found for Si and Ge but not that of Pb (Shvartsburg & Jarrold 1999). Tin cluster anions have not been investigated as much as the cations; recent reviews of the literature can be found in Oger et al (2009) and Lechtken et al (in preparation). We just mention the recent work of Cui et al (2006) in which the existence of a relatively stable Sn 2− 12 dianion with a perfect icosahedral structure was inferred from the photoelectron spectrum of KSn − 12 .…”
Section: Tin Cluster Anions: From Spherical To Prolate To Clusters Ofmentioning
confidence: 99%
“…Note that in all comparative IMS and TIED studies performed so far on metal clusters we have observed no indication for metastable species. [36][37][38] One possible explanation for these findings is that isomer II is lost before the structure dependent measurement is taken, i.e., during injection into the drift cell in IMS or during trapping in the TIED experiment. In both cases a fraction of the lab frame kinetic energy (∼300 eV IMS, ∼25 eV TIED) is converted (via collisions with helium) into internal excitation of the cluster.…”
Section: A Structuresmentioning
confidence: 96%